Simple Electrodeposition of Dendritic Pd Without Supporting Electrolyte and Its Electrocatalytic Activity Toward Oxygen Reduction and H2O2 Sensing. Issue 12 (26th November 2013) - Kang, Minkyung; Yang, Yejin; Shim, Jun Ho; Lee, Sang Cheol; Lee, Youngmi; Lee, Chongmok
Abstract Metallic palladium (Pd) electrocatalysts for oxygen reduction and hydrogen peroxide (H2O2) oxidation/reduction are prepared via electroplating on a gold metal substrate from dilute (5 to 50 mM) aqueous K2PdCl4 solution. The best Pd catalyst layer possessing dendritic nanostructures is formed on the Au substrate surface from 50 mM Pd precursor solution (denoted as Pd‐50) without any additional salt, acid or Pd templating chemical species. The Pd‐50 consisted of nanostructured dendrites of polycrystalline Pd metal and micropores within the dendrites which provide high catalyst surface area and further facilitate reactant mass transport to the catalyst surface. The electrocatalytic activity of Pd‐50 proved to be better than that of a commercial Pt (Pt/C) in terms of lower overpotential for the onset and half‐wave potentials and a greater number of electrons (n) transferred. Furthermore, amperometric i–t curves of Pd‐50 for H2O2 electrochemical reaction show high sensitivities (822.2 and −851.9 µA mM−1 cm−2) and low detection limits (1.1 and 7.91 µM) based on H2O2 oxidation H2O2 reduction, respectively, along with a fast response (<1 s).